Creative Space: Synergy Between Interior Design and Textured Art Collections - I Ketut Mahendra; Kayla Annabelle Tjendjaja; Masnuna (Soshum: Jurnal Sosial dan Humaniora, 2026)
This study examines the synergy between interior design and the appreciation of texture art through the framework of Csikszentmihalyi’s Creative Systems Theory, focusing on the interaction among individual, domain, and social dimensions in shaping the creative practices of collector-designers. A qualitative phenomenological approach was employed, with data obtained through semi-structured in-depth interviews with professional interior designers who are also active collectors of texture art. The analysis was conducted using a systematic thematic approach based on the three dimensions of the theory. The results indicate that the individual dimension is reflected in the integration of design principles and aesthetic sensitivity, flow experiences when interacting with artworks, and reflections on textural expressiveness beyond technical aspects. Domain interaction generates a new aesthetic framework, in which classical design principles enrich material interpretation and exposure to experimental art encourages a paradigm shift toward adaptive approaches. Meanwhile, the field dimension operates through networks with galleries, curators, and artists that facilitate creative dialogue and curatorial intuition. This study contributes to the understanding of cross-disciplinary creativity, showing that innovation emerges through dynamic interactions between individual combinatorial abilities, knowledge exchange across domains, and the support of a creative ecosystem that fosters collaboration and reflection in contemporary design and art practices.